Responsible innovation across societal sectors: a practice perspective on Quadruple Helix collaboration - Johannes Starkbaum; Robert Braun; Vincent Blok; Fabian Schroth; Johann Jakob Häußermann; Claudia Colonnello; Eugen Popa; Renate Wesselink; Anna Gerhardus (Journal of Responsible Innovation)
To address societal challenges, research and innovation approaches, involving a wide range of actors, are increasingly promoted by policy communities. This paper explores the practice of Quadruple Helix collaborations for responsible innovation and how these implement the theoretical ambition of including actors from different societal sectors in innovation, including actors from the fields of arts, media and civil society, which is conceptualized as the Fourth Helix in this concept. Referring to cross-sector collaboration literature and based on an empirical investigation, we explore which actors, representing the Fourth Helix, actually engage in innovation collaborations, how this engagement plays out in practice, and the institutional and systemic dynamics involved in output and value creation. We rely on data from three Social Labs in Austria, Germany, and the Netherlands, which constitute qualitative, change-oriented research processes, where we researched and engaged with actors from cases constituting- or aiming for a Quadruple Helix collaboration. This was accompanied by a desktop study including qualitative interviews of 51 further cases. We find that the actual engagement of actors from civil society is fragile and that forces beyond Quadruple Helix cases impact these quite firmly in some cases.